2019
DOI: 10.1002/14651858.cd012801.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Toric intraocular lens versus limbal relaxing incisions for corneal astigmatism after phacoemulsification

Abstract: Toric intraocular lens versus limbal relaxing incisions for corneal astigmatism a er phacoemulsification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 54 publications
0
39
0
2
Order By: Relevance
“…A meta-analysis of studies that included LRIs made with both manual and femtosecond laser systems suggests that the likelihood of achieving a residual refractive cylinder of ≤0.50 D is higher with a toric IOL. 17 There are limitations to this study. Perhaps most importantly, it was difficult to obtain a significant sample size of matched patients without a large range of follow-up times, but it was felt that the tradeoff for good biometric matches was important.…”
Section: Discussionmentioning
confidence: 90%
“…A meta-analysis of studies that included LRIs made with both manual and femtosecond laser systems suggests that the likelihood of achieving a residual refractive cylinder of ≤0.50 D is higher with a toric IOL. 17 There are limitations to this study. Perhaps most importantly, it was difficult to obtain a significant sample size of matched patients without a large range of follow-up times, but it was felt that the tradeoff for good biometric matches was important.…”
Section: Discussionmentioning
confidence: 90%
“…In total, 60 systematic reviews published between 2005 and 2020 evaluated ophthalmic interventions using quality-oflife outcomes. Seventeen had corresponding authors in the UK, 18,19,23,26,28,29,32,37,[42][43][44]46,[54][55][56][57][58][59] 13 in the US, 13,20,21,38-40,60-66 6 in China, 24,27,30,67-69 6 in Italy, 22,25,70-73 3 in Brazil, 34,45,74 3 in Canada, 14,15,17 2 in Denmark, 75,76 2 in Spain, 33,42 and 1 each in Uruguay, 41 Switzerland, 16 Bahrain, 73 Germany, 77 Belgium, 31 the Netherlands, 36 Taiwan, 35 and Australia. 78 Thirty-nine reviews reported vision-related quality-of-life measures 13,15,16,19,[21][22][23][24][25][26][27][28][29][30][31][32][33][34]37,42,44,54,5...…”
Section: Ophthalmic Interventionsmentioning
confidence: 99%
“…[ 1 ] Residual astigmatism after cataract surgery has been shown to affect the quality of life and reduce patient satisfaction, necessitating its correction with spectacles, limbal relaxing incisions (LRIs) or laser ablative surgery. [ 2 3 4 5 6 ] These approaches suffer from limitations such as lack of precision, chances of regression, variable healing responses, under-correction/over-correction, loss of best spectacle-corrected visual acuity, risk of infection, and post-operative dry eye. [ 2 3 4 5 6 7 ] Also, some patients do not prefer wearing spectacles after cataract surgery.…”
mentioning
confidence: 99%
“…[ 2 3 4 5 6 ] These approaches suffer from limitations such as lack of precision, chances of regression, variable healing responses, under-correction/over-correction, loss of best spectacle-corrected visual acuity, risk of infection, and post-operative dry eye. [ 2 3 4 5 6 7 ] Also, some patients do not prefer wearing spectacles after cataract surgery. The ability of toric IOLs to treat pre-existing corneal astigmatism along with surgical aphakia, particularly in cases of significant corneal astigmatism was shown to provide a substantial advantage over LRIs, or excimer laser surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation